Poças da maré: Análise da pesquisa ecológica e estudo dos padrões de biodiversidade. - Souza, Shayanna Mitri Amorim da Rocha (2020)
The structuring processes of natural systems and their biological response vary depending on the observational scale. Considering the complexity of these processes, this study examined different ecological aspects in rock pools. We analyzed the state of knowledge of scientific research on the topic and described the biodiversity patterns of mollusc assemblages on fine and macro scales. The thesis is organized in three chapters. Chapter 1 consists of a systematic review of the literature. Through a qualitative and quantitative approach, this review synthesized the scientific literature published in the last 25 years, identifying the main knowledge gaps on the topic. These discoveries provided the theoretical basis for construction of the hypotheses of this thesis. The second chapter studied the distribution of rock pool mollusc assemblages at local scale. The study was carried out in pools of three sandstone reefs on the west coast of Ceará and examined the biological structure depending on location and pool size. Chapter 3 investigated pools of eight reefs in Brazilian northeast coast and analyzed compositional variation of assemblages at large scale to identify main explanatory predictors of this variation. The results found that most publications on rock pools were carried out in marine pools of temperate ecosystems and the most studied group was ichthyofauna. At fine scale, there was no correlation between pool size and biological structure of the mollusc assemblages, however this structure was influenced by spatial variation. At the large scale, substrate compositional texture was identified as main explanatory environmental predictor in assemblage variability. However, most of explanation resulted from spatial component. This component is associated with biogeographic processes. We conclude that biogeographic processes drive composition of the regional species pool and that selective environmental filter structure local assemblages. However, most of explanation came from spatial component. This component is associated with biogeographic processes. We conclude that biogeographic processes drive composition of the regional species pool and that selective environmental and biotic filter structure local assemblages at rock pools.